Expression-based analyses indicate a central role for hypoxia in driving tumor plasticity through microenvironment remodeling and chromosomal instability. (December 2018) - Jing, Anqi; Vizeacoumar, Frederick; Parameswaran, Sreejit; Haave, Bjorn; Cunningham, Chelsea; Wu, Yuliang; Arnold, Roland; Bonham, Keith; Freywald, Andrew; Han, Jie; Vizeacoumar, Franco
Abstract Can transcriptomic alterations drive the evolution of tumors? We asked if changes in gene expression found in all patients arise earlier in tumor development and can be relevant to tumor progression. Our analyses of non-mutated genes from the non-amplified regions of the genome of 158 triple-negative breast cancer (TNBC) cases identified 219 exclusively expression-altered (EEA) genes that may play important role in TNBC. Phylogenetic analyses of these genes predict a "punctuated burst" of multiple gene upregulation events occurring at early stages of tumor development, followed by minimal subsequent changes later in tumor progression. Remarkably, this punctuated burst of expressional changes is instigated by hypoxia-related molecular events, predominantly in two groups of genes that control chromosomal instability (CIN) and those that remodel tumor microenvironment (TME). We conclude that alterations in the transcriptome are not stochastic and that early-stage hypoxia induces CIN and TME remodeling to permit further tumor evolution. Tumorigenesis: Hypoxia affects CIN and TME genes simultaneously Altered gene expression is universal in tumors, but does it impact tumor development and progression? A collaborative team lead by Franco Vizeacoumar and Jei Han from Canada's University of Saskatchewan and University of Alberta respectively, analyzed expression of non-mutated and non-amplified genes in Triple-Negative Breast Cancer (TNBC) patients. This exclusively expression-altered genes, included those that regulate chromosomal instability (CIN) and remodeling of tumor microenvironment (TME). Further analyses predict hypoxia induced a "punctuated burst" of changes in expression patterns of genes involved in CIN and TME, driving early stages of tumor development. This work provides a novel strategy to co-inhibit CIN and TME genes to disrupt tumor development.